LUBAC Suppresses IL-21-Induced Apoptosis in CD40-Activated Murine B Cells and Promotes Germinal Center B Cell Survival and the T-Dependent Antibody Response - Wang, Jingwei; Li, Tianbao; Zan, Hong; Rivera, Carlos E.; Yan, Hui; Xu, Zhenming (Frontiers in Immunology, 2021)
B cell activation by Tfh cells, i.e., through CD154 engagement of CD40 and IL-21, and survival within GCs are crucial for the T-dependent Ab response. LUBAC, composed of HOIP, SHARPIN and HOIL-1, catalyzes linear ubiquitination (Linear M1-Ub) to mediate NF-kappaB activation and cell survival induced by TNF receptor superfamily members, which include CD40. As shown here, B cells expressing the Sharpin null mutation cpdm (Sharpincpdm) could undergo proliferation, CSR and SHM in response to immunization by a T-dependent Ag, but were defective in survival within GCs, enrichment of a mutation encoding high-affinity BCRs and production of specific Abs. Sharpincpdm B cells stimulated in vitro with CD154 displayed normal proliferation and differentiation, marginally impaired NF-B activation and survival, but markedly exacerbated death triggered by IL-21. While activating the mitochondria-dependent apoptosis pathway in both Sharpin+/+ and Sharpincpdm B cells, IL-21 induced Sharpincpdm B cells to undergo sustained activation of caspase 9 and caspase 8 of the mitochondria-dependent and -independent pathway, respectively, and ultimately caspase 3 in effecting apoptosis. These were associated with loss of caspase 8 inhibitor cFLIP and reduction in cFLIP Linear M1-Ub, which interferes with cFLIP poly-ubiquitination at Lys48 and degradation. Finally, the viability of Sharpincpdm B cells was rescued by caspase inhibitors, but virtually abrogated – together with Linear M1-Ub and cFLIP levels – by a small molecule HOIP inhibitor. Thus, LUBAC controls cFLIP expression and inhibits the effects of caspase 8 and IL-21-activated caspase 9, thereby suppressing apoptosis of CD40 and IL-21-activated B cells and promoting GC B cell survival.